Penggunaan Media Sosial Tiktok dalam Proses Pembelajaran - Fitri Fajriani; Nabila Nur Aprilia; Izhar Harahap; Sri Mulyeni (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to explore the utilization of the social media platform TikTok in supporting the learning process in the digital era. TikTok, as a popular platform offering various creative features, has the potential to become a learning tool that captures students' attention and enhances their engagement. The research employs a qualitative descriptive method, with data collected through observation, interviews, and content analysis. The results indicate that using TikTok in education can increase students' interest in learning materials, expand teaching methods, and provide a more innovative and enjoyable learning experience. However, challenges such as time management and the risk of distractions must be addressed to ensure the effective use of TikTok. This study concludes that, with the right strategies, TikTok can serve as a relevant and beneficial learning medium, aligned with the evolving educational needs of the digital era.